Synthesis, Characterization, and Histological Evaluation of Chitosan-Ruta Graveolens Essential Oil Films (2020)
The development of new biocompatible materials for application in the replacement of deteriorated tissues (due to accidents and diseases) has gained a lot of attention due to the high demand around the world. Tissue engineering o ers multiple options from biocompatible materials with easy resorption. Chitosan (CS) is a biopolymer derived from chitin, the second most abundant polysaccharide in nature, which has been highly used for cell regeneration applications. In this work, CS films and Ruta graveolens essential oil (RGEO) were incorporated to obtain porous and resorbable materials, which did not generate allergic reactions. An oil-free formulation (F1: CS) and three di erent formulations containing R. graveolens essential oil were prepared (F2: CS-RGEO 0.5%; F3: CS+RGEO 1.0%; and F4: CS+RGEO 1.5%) to evaluate the e ect of the RGEO incorporation in the mechanical and thermal stability of the films. Infrared spectroscopy (FTIR) analyses demonstrated the presence of RGEO. In contrast, X-ray di raction (XRD) and di erential scanning calorimetry (DSC) analysis showed that the crystalline structure and percentage of CS were slightly a ected by the RGEO incorporation. Interesting saturation phenomena were observed for mechanical and water permeability tests when RGEO was incorporated at higher than 0.5% (v/v). The results of subdermal implantation after 30 days in Wistar rats showed that increasing the amount of RGEO resulted in greater resorption of the material, but also more significant inflammation of the tissue surrounding the materials. On the other hand, the thermal analysis showed that the RGEO incorporation almost did not a ect thermal degradation. However, mechanical properties demonstrated an understandable loss of tensile strength and Young’s modulus for F3 and F4. However, given the volatility of the RGEO, it was possible to generate a slightly porous structure, as can be seen in the microstructure analysis of the surface and the cross-section of the films. The cytotoxicity analysis of the CS+RGEO compositions by the hemolysis technique agreed with in vivo results of the low toxicity observed. All these results demonstrate that films including crude essential oil have great application potential in the biomedical field.